Educação profissional técnica: concepção docente na perspectiva de uma educação humanizadora - Mota, Cinthya Raquel Pimentel da (2018)
The technical professional education has been developed to meet the demands of the world of work and its characteristics are noticeable today. The present dissertation analyzes the teaching conceptions from the perspective of a humanizing education in the technical professional education of the Federal Institute of Paraíba, from the technical course on Waterway Transportation of the Campus Advanced Cabedelo Center. During the investigation, we reflect on the process of historical development of Brazilian education, making a cut on professional technical education, drawing a relationship on the inseparability between education and work. Next, we discuss humanizing education, based on an ethical and responsible relationship, as well as the importance of the teaching role in this perspective. We delimit as a epistemological path the qualitative approach, of an exploratory and descriptive character. The methodology was divided into three moments: a survey of the published bibliography on the subject in question; the analysis of the pedagogical plan of the course; and semi-structured interviews with five Campus teachers. The analysis of the data obtained in the interviews was based on data analysis, based on the classification of categories followed by the interpretation of the data. As a result, we find that the course arose from the need to fill a gap in the formation of waterways in the region. We note that even taking into account the technical preparation, there is a concern on the part of the teachers in the formation of the individual as a whole, emphasizing that it is not possible to separate theory and practice, demands of the work and the reality of the student. We still perceive difficulties regarding the internships and the lack of laboratories focused on the course. An alarming fact, highlighted by teachers is the lack of investments for continuing education, which hampers improvements for the course. From the results obtained, we realized that our research is the first step to reflect on the subject at the IFPB and we concluded that technical education combined with a humanizing education is fundamental for the professional and personal training of each student.